Promoter aberrant methylation status of ADRA1A is associated with hepatocellular carcinoma. Issue 6 (2nd July 2020) - Chen, Guoqiao; Fan, Xiaoxiao; Li, Yirun; He, Lifeng; Wang, Shanjuan; Dai, Yili; Bin, Cui; Zhou, Daizhan; Lin, Hui
ABSTRACT: The aim of our study was to explore the relationship between the methylation status of the alpha-1A adrenergic receptor ( ADRA1A ) gene and hepatocellular carcinoma (HCC). We combined our in-house data-set with the Cancer Genome Atlas (TCGA) data-set to screen and identify the methylation status and expression of adrenergic receptor (AR) genes in HCC. Immunohistochemistry and western blot were performed to assess the expression of ADRA1A in HCC cell lines and tissues. We further evaluated the methylation levels of the ADRA1A promoter region in 160 HCC patients using the Sequenom MassARRAY® platform and investigated the association between methylation of ADRA1A and clinical characteristics. The expression levels of ADRA1A mRNA and protein were significantly decreased in HCC tissues. Compared with that in paired normal tissues, the mean methylation level of the ADRA1A promoter region was significantly increased in tumour tissues from 160 HCC patients (25.2% vs. 17.0%, P < 0.0001). We found that a DNA methyltransferase inhibitor (decitabine) could increase the expression of ADRA1A mRNA in HCC cell lines. Moreover, hypermethylation of the ADRA1A gene in HCC samples was associated with clinical characteristics, including alcohol intake (P = 0.0097) and alpha-fetoprotein (P = 0.0411). Receiver operator characteristic (ROC) curve analysis demonstrated that the mean methylation levels of ADRA1A could discriminate between HCC tissues and adjacent non-cancerous tissues (AUC = 0.700, P < 0.0001). mRNA sequencing indicated that the main enriched pathways were pathways in cancer, cytokine-cytokine receptor interaction and metabolic pathways (P < 0.01). ADRA1A gene hypermethylation might contribute to HCC initiation and is a promising biomarker for the diagnosis of HCC.